First I want to give you some context. Then I will ask my questions. I think that my questions are easy and fast to answer, so I've decided to put them together in one question here.


Consider the equations $ a_1x_1^{l_1} + \dots + a_rx_r^{l_r} = b $ with $a_1, \dots , a_r \in F^{*}$, where $F$ is a finite field. Let us say that $F$ has $m$ elements. $N$ is the number of solutions. Now I know that if $b \neq 0$ :

$ N = m^{r-1} + \sum \chi_1\chi_2\cdots\chi_r(b) \chi_1(a_1^{-1})\chi_2(a_2^{-1})\cdots\chi_r(a_r^{-1})J(\chi_1,\dots,\chi_r)$. The summation is over $r$-tuples of characters $\chi_1, \dots, \chi_r$, where $ \chi_i^{l_i} = \varepsilon $ and $\chi_i \neq \epsilon$ for $i = 1, \dots, r$.

I want to specializing this to $x^2 + y^4 = 1$. Obviously $r=2$. So I want to sum over all $2$-tuples of characters $\chi_1, \chi_2$ where $ \chi_i^{l_i} = \varepsilon $ and $\chi_i \neq \epsilon$ for $i = 1,2$.

So the $N = m + J(\rho,\chi) + J(\rho,\chi^2) + J(\rho,\chi^3)$, where $\rho$ is a character of order $2$ and $\chi$ is a character of order $4$.


1) Why $\chi^2 = \rho$ ? I need that to say $J(\rho,\chi^2) = -1 $.

2) We know $\chi^4 = \varepsilon$, but why this is enough to say that $\chi^3 = \bar{\chi}$ ?

3) Why $J(\rho,\bar{\chi}) = \overline{J(\rho,\chi)} $ ?

4) Now let us say that $\pi = -J(\rho,\chi)$. We know that $\rho$ takes the values $\pm1$ and $\chi \pm1$, $\pm i$. Why is this enougth to say that $\pi = a+bi$?

5)If my four questions are answered I can say that $N = m - 1 - \pi - \bar{\pi}$ . I know that $ a^2 + b^2 = \pi \bar{\pi} = m $. Why can I say that $N = m - 1 - 2a$ ?

I hope that my question are clear. Sorry that they might be trivial for you. I'm an absolute beginner.


$\chi^2$ has order $2$ and $\rho$ is the only character of order $2$.



$J(\rho,\chi)$ is the sum of terms all of which have the form $\pm1$ or $\pm i$.


  • $\begingroup$ Thank you for your answer. I get it now. Happy new year :). $\endgroup$ – Memories Jan 1 at 18:34
  • $\begingroup$ Sorry for disturbing you again, but can I ask you one final question? My question seems so simple that it wouldnt be necessary to use " ask Question". I showed now $ \rho(a) -1 \equiv 0 (2) $ and $\chi(a) -1 \equiv 0(1+i)$. Combine this to get $(\rho(a) -1)(\chi(b) -1) \equiv 0(2+2i)$. Thus $\sum_{a+b=1} (\rho(a) -1)(\chi(b) -1) \equiv 0(2+2i)$. I have expanded this term and got $\sum_a \rho(a)$ and $\sum_b \chi(b)$. Now I need that these two sum are zero. But I don't see why. $\endgroup$ – Memories Jan 2 at 16:46
  • 1
    $\begingroup$ @Memories It's a general fact about characters that the values of a non-trivial character sum to zero. $\endgroup$ – Lord Shark the Unknown Jan 2 at 16:51

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.